The New Era of Retinal Imaging in Hypertensive Patients. Issue 2 (March 2022) - Tan, Wilson; Yao, Xinwen; Le, Thu-Thao; Tan, Bingyao; Schmetterer, Leopold; Chua, Jacqueline
Abstract : Abstract: Structural and functional alterations in the microcirculation by systemic hypertension can cause significant organ damage at the eye, heart, brain, and kidneys. As the retina is the only tissue in the body that allows direct imaging of small vessels, the relationship of hypertensive retinopathy signs with development of disease states in other organs have been extensively studied; large-scale epidemiological studies using fundus photography and advanced semi-automated analysis software have reported the association of retinopathy signs with hypertensive end-organ damage includes the following: stroke, dementia, and coronary heart disease. Although yielding much useful information, the vessels assessed from fundus photographs remain limited to the larger retinal arterioles and venules, and abnormalities observed may not be that of the earliest changes. Newer imaging modalities such as optical coherence tomography angiography and adaptive optics technology, which allow a greater precision in the structural quantification of retinal vessels, including capillaries, may facilitate the assessment and management of these patients. The advent of deep learning technology has also augmented the utility of fundus photographs to help create diagnostic and risk stratification systems. Particularly, deep learning systems have been shown in several large studies to be able to predict multiple cardiovascular risk factors, major adverse cardiovascular events within 5 years, and presence of coronary artery calcium, from fundus photographs alone. In the future, combining deep learning systems with the imaging precision offered by optical coherence tomography angiography and adaptive optics could pave way for systems that are able to predict adverse clinical outcomes even more accurately.